The removal of arsenic from solution through biochar-enhanced precipitation of calcium-arsenic derivatives. (1st January 2022) - Zama, Eric F.; Li, Gang; Tang, Yu-Ting; Reid, Brian J.; Ngwabie, Ngwa M.; Sun, Guo-Xin
Abstract: Arsenic (As) pollution remains a major threat to the quality of global soils and drinking water. The health effects of As pollution are often severe and have been largely reported across Asia and South America. This study investigated the possibility of using unmodified biochar derived from rice husk (RB) and aspen wood (WB) at 400 °C and 700 °C to enhance the precipitation of calcium/arsenic compounds for the removal of As(III) from solution. The approach was based on utilizing calcium to precipitate arsenic in solution and adding unmodified biochar to enhance the process. Using this approach, As(III) concentration in aqueous solution decreased by 58.1% when biochar was added, compared to 25.4% in the absence of biochar. Varying the pH from acidic to alkaline enabled an investigation into the pH dependent dynamics of the approach. Results indicated that significant precipitation was only possible at near neutral pH (i.e. pH = 6.5) where calcium arsenites (i.e. Ca(AsO2 )2, and CaAsO2 OH½H2 O) and arsenates (i.e. Ca5 (AsO4 )3 OH) were precipitated and deposited as aggregates in the pores of biochars. Arsenite was only slightly precipitated under acidic conditions (pH = 4.5) while no arsenite was precipitated under alkaline conditions (pH = 9.5). Arsenite desorption from wood biochar was lowest at pH 6.5 indicating that wood biochar was able to retain a large quantity of the precipitates formed at pH 6.5 compared to pH 4.5 and pH 9.5. Given that the removal of As(III) from solution is often challenging and that biochar modification invites additional cost, the study demonstrated that low cost unmodified biochar can be effective in enhancing the removal of As(III) from the environment through Ca–As precipitation. Graphical abstract: Image 1 Highlights: Biochar was used to improve the precipitation of arsenic with calcium compounds. Added biochar doubled the removal of arsenic by 58.1% compared to 25.4% without biochar. Precipitates formed included Ca(AsO2 )2, CaAsO2 OH.½H2 O, Ca5 (AsO4 )3 OH, deposited in biochar pores. The pH of solution and biochar type significantly affected the precipitation process. Arsenic desorption was lowest on wood biochar (<0.3%) compared to rice husk biochar (3.2%).